The Effect of Price Earnings Ratio, Debt to Equity Ratio, Net Profit Margin, and Total Asset Turnover on Stock Returns on The Kompas 100 Index - Hocky, Agus; Pasaribu, Yulika Br; Junita, Rika; Putra, Rizaldi; Syahputra, Hidayat (International Conference on Business Management and Accounting, 2023)
This study aims to determine the effect of Price Earnings Ratio, Debt to Equity Ratio, Net Profit Margin, and Total Asset Turnover on Stock Returns on the Kompas 100 Index. The population and samples used in this study were to use purposive sampling methods that were selected based on certain criteria that were in accordance with the study. Thus, the number of samples in this study was 44 companies. The analysis method in this study is multiple linear analysis with the help of SPSS. The results of the research obtained Price Earnings Ratio, Debt to Equity Ratio, Total Asset Turnover did not have a significant effect, then Net Profit Margin had a significant result in Stock Returns.